Comparison of carbohydrate sources for the early-weaned pig - C A Kerr; Steven S Dritz; Robert D Goodband; Jim L Nelssen; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1993)
A total of 180 weanling pigs (initially 11.7 lb and 21 d of age) was used in a 35 d growth assay to compare various carbohydrate sources from d 0 to 14 postweaning in phase I. Pigs were allotted by weight and ancestry to one of five experimental diets with six pigs per pen and six replications per treatment. Pigs were fed one of five experimental diets from d 0 to 14 postweaning. The experimental carbohydrate sources compared were corn, oat flour, two modified potato starches, and lactose. All pigs were then fed a common phase II diet from d 14 to 35 postweaning. For the phase I period, pigs consuming the modified potato starch 1 diet had higher average daily gain (ADG) and average daily feed intake (ADFI) than pigs consuming the corn or oat flour diets. Pigs consuming the modified potato starch 1 diet had numerically higher ADG and ADFI than pigs fed the other four diets. The performance of pigs consuming the modified potato starch 1 diets warrants further investigation. Currently, the hygroscopic nature of modified potato starches prohibits regular application in starter pig diets, because it causes problems in feed manufacturing and ingredient handling. Pigs consuming the lactose diets had higher ADG than the pigs consuming the corn diet. During the phase II (d 14 to 35 postweaning) and cumulative (d 0 to 35 postweaning) periods, no differences occurred in growth performance. Thus, economics indicate no additional inclusion of lactose in the phase I diet above 18% (25% dried edible grade whey). No differences occurred in performance for any phase of the experiment between the pigs consuming the corn or oat flour diets. In conclusion, oat flour does not appear to be a better carbohydrate source than corn in the phase I nursery diet.; Swine Day, Manhattan, KS, November 18,1993
Keywords: Swine day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-194-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 695; Swine; Starter; Carbohydrate